2012
DOI: 10.18585/inabj.v4i3.176
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein and Matrix Metalloproteinase-9 are Associated with Outcome of Ischemic Stroke

Abstract: BACKGROUND: C-Reactive protein (CRP) and matrix metalloproteinase (MMP)-9 are inflammatory mediators that are often associated with the evolution of stroke. In this study, we aimed to find out whether concentration of these biomarkers were associated with the severity of discharge National Institute of Health Stroke Scale (NIHSS) in ischemic stroke patient.METHODS: In prospective stody, we involved 143 ischemic stroke patient who were admitted to hospital not more than 72 hours after the onset and who met the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…(1,2) This has been provoking a lot of studies to find out a better understanding on stroke therapy in the last decades. (3,4) Multiple clinical trials showed sudden decrease of cerebral blood flow (CBF) that can lead to a complex pathophysiology of ischemic cascade including excitotoxicity, inflammation, oxidative damage and ion imbalance, which lead to cerebral infarct CBF restoration either spontaneously or by reperfusion therapy, is needed in time to recover glial and neuron cells after ischemic injury. Recent studies are still focusing on how to improve CBF effectively.…”
Section: Introductionmentioning
confidence: 99%
“…(1,2) This has been provoking a lot of studies to find out a better understanding on stroke therapy in the last decades. (3,4) Multiple clinical trials showed sudden decrease of cerebral blood flow (CBF) that can lead to a complex pathophysiology of ischemic cascade including excitotoxicity, inflammation, oxidative damage and ion imbalance, which lead to cerebral infarct CBF restoration either spontaneously or by reperfusion therapy, is needed in time to recover glial and neuron cells after ischemic injury. Recent studies are still focusing on how to improve CBF effectively.…”
Section: Introductionmentioning
confidence: 99%